Aktivitas Antioksidan Ekstrak Tunggal dan Kombinasinya dari Tanaman Curcuma spp. - FAUZY RACHMAN; EMELIA DEVI LOGAWA; HARUMI HERGATIKA; PARTOMUAN SIMANJUNTAK (Fakultas Farmasi Universitas Pancasila, 2008)
The aim of this research is to investigate the antioxidant activity of the simple extract and its combination from the rhizome of temulawak (Curcuma xanthorriza), temu giring (Curcuma heyneana), temu ireng (Curcuma aeruginosa), and kunyit (Curcuma Zonga) using the free radical scavenging effect methode namely DPPH (1,1-difenil-2-pikrilhidrazil). The use of combination extract is to explore, wether the antioxidant activity are sinergistic or antagonistic. The rhizomes of each plants were extracted With methanol, then partionated to n-hexane. The result indicated that the single methanol extract of kunyit(Curcuma Ionga) at 100 ppm showed the biggest activity (90.04%), While the combination extract of temulawak (Curcuma xanthorriza) and kunyit (Curcuma Zonga) performed the biggest scavenging activity (98.75%) by ratio 1:1.